EUCS, IPA, AND CSI INTEGRATION TO DETECT UBSI ONLINE EXAM SYSTEM SATISFACTION - Sucipto, Rakhmat Hadi; Indrarti, Wahyu; Hussaen, Saddam; Rani, Rani (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2025)
Abstract: The online exam system is used to evaluate student learning, but it has some limitations. Therefore, it is necessary to research the user satisfaction of the system. This study aims to assess user satisfaction using the End User Computing Satisfaction (EUCS), Importance Performance Analysis (IPA), and Customer Satisfaction Index (CSI) methods. The results showed that three dimensions, namely, accuracy, ease of use, and timeliness significantly affected user satisfaction, while content and format did not have a significant effect. IPA analysis shows the majority of attributes (12 attributes) are in quadrant II, which indicates moderate satisfaction, 11 attributes in quadrant III, one attribute in quadrant I, and three attributes in quadrant IV. CSI concluded that the online exam system provides satisfactory service with a score of 77.54%. Keywords: csi; eucs; ipa; online exam system; user satisfaction  Abstrak: Sistem ujian online digunakan untuk mengevaluasi pembelajaran mahasiswa, tetapi sistem ini memiliki beberapa keterbatasan. Karena itulah perlu penelitian kepuasan pengguna sistem tersebut. Penelitian ini bertujuan menilai kepuasan pengguna dengan menggunakan metode End User Computing Satisfaction (EUCS), Importance Performance Analisys (IPA), dan Customer Satisfaction Index (CSI). Hasil riset menunjukkan tiga dimensi yaitu, akurasi, kemudahan penggunaan, dan ketepatan waktu signifikan mempengaruhi kepuasan pengguna, sementara konten dan format tidak berpengaruh signifikan. Analisis IPA menunjukkan mayoritas atribut (12 atribut) berada di kuadran II, yang mengindikasikan kepuasan sedang, 11 atribut di kuadran III, satu atribut di kuadran I, dan tiga atribut di kuadran IV. CSI menyimpulkan sistem ujian online memberikan layanan yang memuaskan dengan skor 77,54%. Kata kunci: csi; eucs; ipa; kepuasan pengguna; sistem ujian online